PENGARUH AUDIT DELAY, AUDIT FEE, DAN UKURAN PERUSAHAAN TERHADAP AUDITOR SWITCHING (STUDI PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI TERDAFTAR DI BEI 2016-2019) - Catherina Stevani; Valentine Siagian (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
This study aims to determine the effect of audit delay, audit fee, and company size on auditor switching by a company. Based on the type of data, this study uses quantitative research methods, which are then processed using SPSS software. With the purposive sampling method, the research sample obtained was 30 companies in the consumer goods industry sector listed on Indonesia Stock Exchange for the year 2016-2019. This study uses Audit Delay, Audit Fee, and Company Size as the dependent variable and Auditor Switching as the independent variable. This research uses descriptive analysis, multicollinearity test, t-test and F test as statistical analysis instruments. The results of the research through the t-test shows that audit delay has a significant effect on auditor switching, audit fees have no significant effect on auditor switching, and company size does not have a significant effect on auditor switching. Coefficient determination shows that audit delay, audit fees, and company size affect auditor switching 6,8% and F test shows a significant effect.